Loss estimation for landslides in mountain areas – An integrated toolbox for vulnerability assessment and damage documentation. (January 2015) - Papathoma-Köhle, M.; Zischg, A.; Fuchs, S.; Glade, T.; Keiler, M.
Abstract: Global environmental change includes changes in a wide range of global scale phenomena, which are expected to affect a number of physical processes, as well as the vulnerability of the communities that will experience their impact. Decision-makers are in need of tools that will enable them to assess the loss of such processes under different future scenarios and to design risk reduction strategies. In this paper, a tool is presented that can be used by a range of end-users (e.g. local authorities, decision makers, etc.) for the assessment of the monetary loss from future landslide events, with a particular focus on torrential processes. The toolbox includes three functions: a) enhancement of the post-event damage data collection process, b) assessment of monetary loss of future events and c) continuous updating and improvement of an existing vulnerability curve by adding data of recent events. All functions of the tool are demonstrated through examples of its application. Highlights: We developed a tool that will support decision making for disaster risk reduction strategies in mountain areas. The tool incorporates three functions: damage documentation, loss estimation and updating of the vulnerability curve. The tool was applied and tested in South Tyrol, Italy. Future developments (more elements at risks and hazards, uncertainty analysis, mobile applications) have been pointed out.